Black phosphorus carbon negative electrode, synthesis method and synthesis equipment thereof, and battery comprising black phosphorus carbon negative electrode

By gasifying and catalyzing the formation of gas-phase black phosphorus, depositing it into porous carbon and coating it with carbon, the problems of difficult preparation of black phosphorus and instability of composite materials are solved, and the performance improvement and cost advantages of black phosphorus carbon negative electrode are achieved.

CN119812276APending Publication Date: 2025-04-11SICC CO LTD

Patent Information

Application Number
CN202510017292.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the preparation of black phosphorus is difficult and costly. Uneven dispersion of black phosphorus in composite materials leads to side reactions, and volume changes lead to the shed of the pole sheet, affecting battery performance.

Method used

Inexpensive phosphorus materials such as red phosphorus are used to gasify and catalyze to generate gas-phase black phosphorus, deposit it into porous carbon, and a layer of carbon is coated on the outer layer to form a black phosphorus carbon negative electrode.

Benefits of technology

The preparation cost of black phosphorus carbon negative electrode is reduced, the embedded strength and distribution ratio of black phosphorus in the porous carbon is increased, the battery performance is enhanced and side reactions are prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812276A_ABST
    Figure CN119812276A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery negative electrode materials, and particularly relates to a black phosphorus carbon negative electrode, a synthesis method and synthesis equipment thereof and a battery comprising the black phosphorus carbon negative electrode. The black phosphorus carbon negative electrode comprises porous carbon, black phosphorus loaded in the porous carbon and coating carbon for coating the porous carbon, the black phosphorus is deposited into the porous carbon after gas-phase phosphorus except the black phosphorus is subjected to catalytic conversion, and the mass ratio of the black phosphorus is 10%-80%. Cheap phosphorus materials such as red phosphorus are used as raw materials, gas-phase black phosphorus is formed through gasification and catalysis and is deposited into porous carbon under the action of temperature difference, then the outermost layer is coated with a layer of coating carbon to obtain the black phosphorus carbon negative electrode, the performance of the negative electrode material is improved, and the cost advantage is obvious.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode materials, and in particular relates to a black phosphorus carbon negative electrode and a synthesis method and synthesis equipment thereof, and a battery comprising the same. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Although graphite and other carbon materials have been widely used as relatively mature negative electrode materials in the market, their maximum capacity is only 372 mAh / g, which means that ion batteries using graphite and other carbon materials as negative electrodes have reached their limits. In order to improve energy density, high-capacity phosphorus has become a development target. The theoretical capacity of phosphorus at room temperature can reach 2596 mAh / g, which has a huge capacity advantage over graphite. Compared with red phosphorus, black phosphorus has a higher ion mobility, and its hole mobility is as high as 1000 cm 2 / v / s, which makes black phosphorus more advantageous in the application of ion batteries.

[0004] Although black phosphorus has advantages in theoretical capacity, ion mobility and hole mobility, black phosphorus as a semiconductor material has poor electrical conductivity, is prone to large volume expansion and contraction during the charge and discharge process, and has poor cycle stability. The prior art uses ball milling, vapor deposition, solvothermal method and other methods to compound black phosphorus with carbon materials such as graphite and conductive carbon black to improve the conductivity of the negative electrode material and inhibit its volume change during the charge and discharge process, thereby improving battery performance. For example, CN116573621A discloses a black phosphorus-carbon composite material and its preparation method and application, wherein black phosphorus and carbon materials are reacted in an organic amine solvent at 80 to 200°C to obtain the black phosphorus and carbon composite material. For example, CN117673304A discloses a phosphorus-carbon composite negative electrode material and its preparation method and application, wherein a phosphorus source is deposited on a carbon source by chemical vapor deposition to obtain a phosphorus-carbon composite negative electrode material. Although black phosphorus and carbon are compounded in the prior art, the following problems still exist:

[0005] (1) The difficulty in preparing black phosphorus leads to its high price, making it expensive to use black phosphorus as a raw material for preparing phosphorus-carbon negative electrodes. The traditional method for preparing black phosphorus requires mixing the raw material red phosphorus with a catalyst through ball milling before reacting, and the resulting black phosphorus contains catalyst impurities.

[0006] (2) Although black phosphorus and carbon are compounded by ball milling, vapor deposition, solvothermal method, etc., a large amount of black phosphorus in the composite material is dispersed on the carbon surface and directly contacts with the electrolyte in the battery, resulting in side reactions;

[0007] (3) The composite material has a limited degree of restriction on the volume change of black phosphorus. The volume change of black phosphorus will cause the electrode to fall off, thus affecting the battery performance. Summary of the invention

[0008] In order to solve the deficiencies of the prior art, the present invention provides a black phosphorus carbon negative electrode and a synthesis method and synthesis equipment thereof, and a battery including the same. The present invention uses cheap phosphorus materials such as red phosphorus as raw materials, gasifies and catalyzes to form gas phase black phosphorus, and deposits it into porous carbon under the action of temperature difference, and then coats the outermost layer with a layer of coated carbon to obtain a black phosphorus carbon negative electrode, which improves the performance of the negative electrode material and has obvious cost advantages.

[0009] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0010] In a first aspect, the present invention provides a black phosphorus carbon negative electrode, comprising porous carbon, black phosphorus loaded in the porous carbon, and coated carbon coating the porous carbon, wherein the black phosphorus is deposited into the porous carbon after catalytic conversion of gaseous phase phosphorus other than black phosphorus, and the mass proportion of the black phosphorus is 10% to 80%.

[0011] Preferably, the mass percentage of the black phosphorus is 30% to 65%.

[0012] Still more preferably, the mass proportion of the black phosphorus is 40% to 60%.

[0013] Preferably, the ratio of the specific surface area of ​​the porous carbon to the specific surface area of ​​the black phosphorus carbon negative electrode is 100-2000, and the ratio of the average pore size of the porous carbon to the average pore size of the black phosphorus carbon negative electrode is 1-100.

[0014] Preferably, the average particle size of the porous carbon is 1-10 μm in terms of D50, the microporosity of the porous carbon is 60%-90%, the average pore size of the porous carbon is 1.2-50 nm, and the specific surface area of ​​the porous carbon is 400-3000 m 2 / g, the particle size distribution law R of porous carbon is 0.1~2, where R=(D90-D10) / D50.

[0015] More preferably, the average particle size of the porous carbon is 2 to 8 μm in terms of D50.

[0016] Still more preferably, the average particle size of the porous carbon is 4 to 6 μm in terms of D50.

[0017] More preferably, the microporosity of the porous carbon is 80% to 90%.

[0018] More preferably, the specific surface area of ​​the porous carbon is 1000 to 2000 m 2 / g.

[0019] More preferably, the particle size distribution law R of the porous carbon is 0.15-1.

[0020] Still more preferably, the particle size distribution law R of the porous carbon is 0.2 to 0.6.

[0021] Preferably, the gas phase phosphorus includes at least one of gas phase red phosphorus, gas phase white phosphorus and gas phase yellow phosphorus; and the thickness of the coated carbon is 2 to 50 nm.

[0022] More preferably, the thickness of the coated carbon is 10 to 30 nm.

[0023] In a second aspect, the present invention provides a method for synthesizing a black phosphorus carbon negative electrode as described in the first aspect, comprising the following steps:

[0024] Phosphorus is heated and gasified into gaseous phosphorus, which is catalyzed by a catalyst to generate gaseous black phosphorus, and the gaseous black phosphorus is deposited in porous carbon to obtain black phosphorus porous carbon, which reacts with a reaction gas containing carbon and hydrogen gas to obtain a black phosphorus carbon negative electrode.

[0025] Preferably, the temperature for heating and gasifying phosphorus is 400℃~1000℃, the temperature for the catalyst is 400℃~600℃, the temperature for the porous carbon is 400℃~600℃, the temperature for the reaction of black phosphorus porous carbon with the reaction gas is 400℃~800℃, and the temperature for heating and gasifying phosphorus is greater than the temperature for the catalyst and the temperature for the porous carbon.

[0026] More preferably, the temperature for heating and gasifying phosphorus is 500°C to 800°C, the temperature of the catalyst is 450°C to 550°C, and the temperature of the porous carbon is 450°C to 550°C.

[0027] Preferably, the black phosphorus porous carbon is reacted with the reaction gas containing carbon and hydrogen gas 18 to 36 hours after the phosphorus is completely gasified.

[0028] Preferably, the catalyst comprises an active substance and a carrier, the constituent elements of the active substance include tin, phosphorus and iodine, the carrier is a honeycomb ceramic or carbon material, and the carbon material includes porous carbon, graphite, soft carbon or hard carbon.

[0029] More preferably, the active material is tin phosphite iodide or tin phosphite iodide bismuth, and the chemical formula of the tin phosphite iodide is Sn 24 P 19.3 I8, the chemical formula of the tin-phosphorus-iodine-bismuth is XSn 24 P 19.3 I8+(1-X)Bi, X=0.01-1 and not 1.

[0030] Preferably, the hydrocarbon gas includes at least one of acetylene, ethylene, methane and propylene, the reaction gas also includes an inert gas, the inert gas includes at least one of nitrogen and argon, the volume ratio of the reaction gas to the inert gas is 1:(1-10), the flow rate of the reaction gas is 1-3 L / min, and the reaction time of the black phosphorus porous carbon and the reaction gas is 1-5 h.

[0031] In the third aspect, the present invention provides a synthesis device for synthesizing the black phosphorus carbon negative electrode as described in the first aspect, including a black phosphorus carbon composite device and a coated carbon synthesis device, wherein the black phosphorus carbon composite device is provided with an independently temperature-controlled phosphorus chamber, a catalyst chamber and a porous carbon chamber in sequence according to the gas flow direction, and closed valves are provided between the phosphorus chamber and the catalyst chamber and between the catalyst chamber and the porous carbon chamber, and the coated carbon synthesis device includes one of a fluidized bed device, a rotary kiln device and a tubular furnace device.

[0032] Preferably, the black phosphorus carbon composite device is horizontal or vertical.

[0033] In a fourth aspect, the present invention provides a battery comprising the black phosphorus carbon negative electrode as described in the first aspect.

[0034] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:

[0035] The present invention utilizes cheap red phosphorus and other phosphorus materials as raw materials, generates gaseous black phosphorus after high-temperature gasification and catalytic conversion, and further deposits it into porous carbon. The red phosphorus conversion ratio is high and there are no impurities in the black phosphorus carbon, which reduces the preparation cost of the black phosphorus carbon negative electrode and improves the embedding strength and distribution ratio of black phosphorus in the porous carbon.

[0036] On the one hand, the present invention deposits black phosphorus into the pores of porous carbon, and on the other hand, a layer of carbon is coated on the outer layer of the porous carbon. The porous carbon provides spatial protection for the expansion of black phosphorus, and the outer layer of coated carbon can prevent black phosphorus from directly contacting the electrolyte and preventing unnecessary side reactions, thereby improving the performance of the black phosphorus carbon negative electrode.

[0037] The present invention generates black phosphorus in one step by gasifying and catalyzing cheap phosphorus such as red phosphorus, and then utilizes vapor deposition to deposit it into porous carbon, and finally forms coated carbon outside the porous carbon. The synthesis method is simple and is conducive to industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0039] Figure 1 A schematic diagram of the structure of a synthesis device for synthesizing a black phosphorus carbon negative electrode;

[0040] Among them, 1 is a phosphorus chamber, 2 is a catalyst chamber, 3 is a porous carbon chamber, and 4 is a closed valve. DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0042] Example 1

[0043] The synthesis equipment used to synthesize the black phosphorus carbon negative electrode includes a black phosphorus carbon composite device and a coated carbon synthesis device. Figure 1 As shown, the black phosphorus carbon composite device is provided with independently temperature-controlled phosphorus chamber 1, catalyst chamber 2 and porous carbon chamber 3 in sequence according to the gas flow direction, and a sealed valve 4 is provided between the phosphorus chamber 1 and the catalyst chamber 2 and between the catalyst chamber 2 and the porous carbon chamber 3. The coated carbon synthesis device is a fluidized bed.

[0044] 60g of red phosphorus was placed in phosphorus chamber 1, 100g of catalyst (XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X=0.5) was placed in the catalyst chamber 2, 48 g of porous carbon (D50 is 5 μm, microporosity is 90%, specific surface area is 1800 m 2 / g, average pore size of 2.2nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 550℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0045] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 5m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 50%, and the thickness of the coated carbon is 30nm.

[0046] The black phosphorus carbon negative electrode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the ratio of black phosphorus carbon negative electrode: conductive agent: hydroxymethyl cellulose (CMC): styrene butadiene rubber (SBR) = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + fluoroethylene carbonate (FEC) + ethylene carbonate (EC) + diethyl carbonate (DEC) system. The test capacity is 1480mAh / g, and the capacity retention rate is 90% after 100 cycles at a current density of 1A / g.

[0047] Example 2

[0048] 55 g of red phosphorus was placed in phosphorus chamber 1, 100 g of catalyst ((XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X=0.6) was placed in catalyst chamber 2, 43 g of porous carbon (D50 is 5 μm, microporosity is 86%, specific surface area is 1700 m 2 / g, average pore size 2.5nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 600℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0049] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 5.2m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 55%, and the thickness of the coated carbon is 30nm.

[0050] The black phosphorus carbon anode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon anode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 1580mAh / g, and the capacity retention rate is 87% after 100 cycles at a current density of 1A / g.

[0051] Example 3

[0052] 60g of red phosphorus was placed in phosphorus chamber 1, 100g of catalyst (XSn24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X=0.7) was placed in catalyst chamber 2, 38 g of porous carbon (D50 is 5 μm, microporosity is 45%, specific surface area is 1500 m 2 / g, average pore size of 7.5nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 650℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0053] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 3.7m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 60%, and the thickness of the coated carbon is 30nm.

[0054] The black phosphorus carbon anode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon anode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 1842mAh / g, and the capacity retention rate is 85% after 100 cycles at a current density of 1A / g.

[0055] Example 4

[0056] 62g of red phosphorus was placed in phosphorus chamber 1, 100g of catalyst (XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X = 0.8) was placed in the catalyst chamber 2, 36 g of porous carbon (D50 is 5 μm, microporosity is 35%, specific surface area is 1400 m 2 / g, average pore size of 10.5nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 700℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0057] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 4.2m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 62%, and the thickness of the coated carbon is 30nm.

[0058] The black phosphorus carbon anode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon anode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 1903mAh / g, and the capacity retention rate is 84% ​​after 100 cycles at a current density of 1A / g.

[0059] Example 5

[0060] 55 g of red phosphorus was placed in phosphorus chamber 1, 100 g of catalyst (XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X = 0.9) was placed in the catalyst chamber 2, 43 g of porous carbon (D50 is 5 μm, microporosity is 75%, specific surface area is 1700 m 2 / g, average pore size of 3.5nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 800℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0061] The obtained black phosphorus carbon negative electrode was characterized. The specific surface area of ​​the black phosphorus carbon negative electrode was 4.3m2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode was 55%, and the thickness of the coated carbon was 30nm.

[0062] The black phosphorus carbon anode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon anode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 1627mAh / g, and the capacity retention rate is 87% after 100 cycles at a current density of 1A / g.

[0063] Example 6

[0064] 50 g of red phosphorus was placed in phosphorus chamber 1, 100 g of catalyst (XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X = 0.95) was placed in the catalyst chamber 2, 48 g of porous carbon (D50 is 5 μm, microporosity is 85%, specific surface area is 1600 m 2 / g, average pore size of 2.5nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 600℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:1, volume ratio) at 600℃ for 4h to obtain a black phosphorus carbon negative electrode.

[0065] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 6m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 45%, and the thickness of the coated carbon is 40nm.

[0066] The black phosphorus carbon negative electrode is configured into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon negative electrode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 1465mAh / g, and the capacity retention rate is 90% after 100 cycles at a current density of 1A / g.

[0067] Example 7

[0068] 59g red phosphorus was placed in phosphorus chamber 1, 100g catalyst (50g Sn 24 P 19.3I8 is the active material, 50 g of porous carbon is the carrier) is placed in the catalyst chamber 2, 39 g of porous carbon (D50 is 5 μm, microporosity is 70%, specific surface area is 1400 m 2 / g, average pore size of 3.7nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 600℃, the catalyst is heated at 550℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. After the red phosphorus is completely gasified for 1 hour, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2 hours to obtain a black phosphorus carbon negative electrode.

[0069] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 3m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 59%, and the thickness of the coated carbon is 30nm.

[0070] The black phosphorus carbon negative electrode is configured into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon negative electrode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 1817mAh / g, and the capacity retention rate is 86% after 100 cycles at a current density of 1A / g.

[0071] Example 8

[0072] 50g red phosphorus was placed in phosphorus chamber 1, 100g catalyst (Sn 24 P 19.3 I8 is 50 g of active material, 50 g of porous carbon is used as a carrier, X = 0.5) is placed in the catalyst chamber 2, 48 g of porous carbon (D50 is 5 μm, microporosity is 90%, specific surface area is 1800 m 2 / g, average pore size of 2.2nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 550℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. 20h after the red phosphorus is completely gasified, the black phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0073] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 5.5m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 40%, and the thickness of the coated carbon is 30nm.

[0074] The black phosphorus carbon negative electrode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the ratio of black phosphorus carbon negative electrode: conductive agent: hydroxymethyl cellulose (CMC): styrene butadiene rubber (SBR) = 92:2:2:3:3, and coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + fluoroethylene carbonate (FEC) + ethylene carbonate (EC) + diethyl carbonate (DEC) system. The test capacity is 1280mAh / g, and the capacity retention rate is 90% after 100 cycles at a current density of 1A / g.

[0075] Comparative Example 1

[0076] 50g of red phosphorus was placed in phosphorus chamber 1, 100g of catalyst (tin iodide as active material, porous carbon as carrier, mass fraction of tin iodide was 50%) was placed in catalyst chamber 2, 50g of porous carbon (D50 was 5μm, microporosity was 75%, specific surface area was 1500m 2 / g, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 600°C, the catalyst is heated at 500°C, and the porous carbon is heated at 450°C. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black red phosphorus porous carbon. 20 hours after the red phosphorus is completely gasified, the black red phosphorus porous carbon is taken out and placed in a fluidized bed, and the reaction gas (acetylene: nitrogen = 1:10, volume ratio) is introduced to react at 600°C for 2 hours to obtain a black red phosphorus carbon negative electrode.

[0077] The obtained black red phosphorus carbon negative electrode was characterized, and the specific surface area of ​​the black red phosphorus carbon negative electrode was 5m 2 / g, the red phosphorus was removed by washing with hydrogen peroxide, the mass fraction of black phosphorus in the black-red phosphorus carbon negative electrode was 15%, and the thickness of the coated carbon was 30nm.

[0078] The black red phosphorus carbon negative electrode (the red phosphorus was not removed by hydrogen peroxide) was prepared into a slurry with a solid content of 40% (the solvent was water) according to the black red phosphorus carbon negative electrode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc was taken to make a pole piece. The button battery was assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte used was sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity was 1141mAh / g, and the capacity retention rate was 68% after 100 cycles at a current density of 1A / g.

[0079] Comparative Example 2

[0080] 50 g of red phosphorus was placed in phosphorus chamber 1, 100 g of catalyst (XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X=0.5) was placed in the catalyst chamber 2, 48 g of carbon black (D50 is 42 μm, microporosity is 10%, specific surface area is 75 m 2 / g, average pore size of 12nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Red phosphorus is heated and gasified at 550℃, the catalyst is heated at 500℃, and the carbon black is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited on the carbon black to generate black phosphorus carbon black. 20h after the red phosphorus is completely gasified, the black phosphorus carbon black is taken out and placed in a fluidized bed, and the reaction gas is introduced at 2L / min (acetylene: nitrogen = 1:10, volume ratio) at 600℃ for 2h to obtain a black phosphorus carbon negative electrode.

[0081] The obtained black phosphorus carbon anode was characterized, and the specific surface area of ​​the black phosphorus carbon anode was 20m 2 / g, the mass fraction of black phosphorus in the black phosphorus carbon negative electrode is 35%, and the thickness of the coated carbon is 30nm.

[0082] The black phosphorus carbon anode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the black phosphorus carbon anode: conductive agent: CMC: SBR = 92:2:2:3:3, coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 967mAh / g, and the capacity retention rate is 80% after 100 cycles at a current density of 1A / g.

[0083] Compared with Example 1, the porous carbon is replaced with carbon black in this comparative example. Due to the low porosity and small specific surface area of ​​carbon black, it is difficult for the gaseous black phosphorus to be uniformly loaded inside the carbon black. Most of it is loaded on the exposed surface of the carbon black, resulting in a decrease in the mass fraction of black phosphorus and a reduction in the negative electrode capacity.

[0084] Comparative Example 3

[0085] 50 g of red phosphorus was placed in phosphorus chamber 1, 100 g of catalyst (XSn 24 P 19.3 I8+(1-X)Bi as active material, 50 g of porous carbon as carrier, X=0.5) was placed in the catalyst chamber 2, 48 g of porous carbon (D50 is 5 μm, microporosity is 90%, specific surface area is 1800 m 2 / g, average pore size of 2.2nm, particle size distribution law R is 1) placed in porous carbon chamber 3. Red phosphorus is heated and gasified at 550℃, the catalyst is heated at 500℃, and the porous carbon is heated at 450℃. The red phosphorus is gasified to generate gas phase red phosphorus, and the gas phase red phosphorus flows to the catalyst and is catalyzed to gas phase black phosphorus. The gas phase black phosphorus is deposited in the porous carbon to generate black phosphorus porous carbon. After the red phosphorus is completely gasified for 20 hours, the black phosphorus porous carbon is taken out.

[0086] The black phosphorus porous carbon was prepared into a slurry with a solid content of 40% (the solvent was water) according to the ratio of black phosphorus porous carbon: conductive agent: CMC: SBR = 92:2:2:3:3, and coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc was taken to make a pole piece. The button cell was assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte used was sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity was 1180mAh / g, and the capacity retention rate was 72% after 100 cycles at a current density of 1A / g.

[0087] In this comparative example, no carbon coating is performed on the basis of Example 1, and black phosphorus porous carbon is directly used as the negative electrode material. Due to the lack of protection of the black phosphorus porous carbon by the outer layer of coated carbon, the capacity of the battery prepared with black phosphorus porous carbon decreases, and the stability is greatly reduced.

[0088] Comparative Example 4

[0089] 50 g of black phosphorus was placed in the phosphorus chamber 1, no catalyst was placed in the catalyst chamber 2, and 48 g of porous carbon (D50 was 5 μm, microporosity was 90%, and specific surface area was 1800 m 2 / g, average pore size of 2.2nm, particle size distribution law R is 1) is placed in the porous carbon chamber 3. Black phosphorus is heated and gasified at 1000°C, the temperature of the catalyst chamber 2 is set to 500°C, and the porous carbon is heated at 450°C. 20 hours after the black phosphorus is completely gasified, the loaded porous carbon is taken out and placed in a fluidized bed, and the reaction gas 2L / min (acetylene: nitrogen = 1:10, volume ratio) is introduced at 600°C for 2 hours to obtain a phosphorus-carbon negative electrode.

[0090] The obtained phosphorus-carbon negative electrode was characterized, and the specific surface area of ​​the phosphorus-carbon negative electrode was 4.5m 2 / g. Since black phosphorus is converted into white phosphorus after gasification, there is no black phosphorus in the phosphorus-carbon negative electrode. The mass fraction of white phosphorus is 53%, and the thickness of the coated carbon is 30nm.

[0091] The phosphorus-carbon negative electrode is prepared into a slurry with a solid content of 40% (the solvent is water) according to the ratio of phosphorus-carbon negative electrode: conductive agent: CMC: SBR = 92:2:2:3:3, and coated on aluminum foil or copper foil, dried, rolled, and a 15mm diameter disc is taken to make a pole piece. The button battery is assembled in the order of sodium sheet, non-woven fabric diaphragm, pole piece, and spring sheet. The electrolyte adopts sodium hexafluorophosphate + FEC + EC + DEC system. The test capacity is 320mAh / g, and the capacity retention rate is 30% after 100 cycles at a current density of 1A / g.

[0092] Compared with Example 1, in this comparative example, black phosphorus is used as a raw material to prepare the negative electrode material by vapor deposition. However, black phosphorus is converted into white phosphorus after gasification, and the obtained phosphorus-carbon negative electrode is composed of white phosphorus and carbon, and a black phosphorus-carbon negative electrode cannot be obtained. Compared with the black phosphorus-carbon negative electrode of the present invention, the phosphorus-carbon negative electrode directly obtained from black phosphorus as a raw material has a significant decrease in both capacity and stability.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A black phosphorus carbon negative electrode, characterized in that: The invention comprises porous carbon, black phosphorus loaded in the porous carbon and coated carbon coating the porous carbon. The black phosphorus is deposited in the porous carbon after catalytic conversion of gas phase phosphorus other than black phosphorus. The mass proportion of the black phosphorus is 10% to 80%.

2. The black phosphorus carbon negative electrode according to claim 1, characterized in that The ratio of the specific surface area of ​​the porous carbon to the specific surface area of ​​the black phosphorus carbon negative electrode is 100-2000, and the ratio of the average pore diameter of the porous carbon to the average pore diameter of the black phosphorus carbon negative electrode is 1-100.

3. The black phosphorus carbon negative electrode according to claim 1, characterized in that The average particle size of the porous carbon is 1 to 10 μm in terms of D50, the microporosity of the porous carbon is 60% to 90%, the average pore size of the porous carbon is 1.2 to 50 nm, and the specific surface area of ​​the porous carbon is 400 to 3000 m 2 / g, the particle size distribution law R of porous carbon is 0.1~2, where R=(D90-D10) / D50.

4. The black phosphorus carbon negative electrode according to claim 1, characterized in that The gas phase phosphorus includes at least one of gas phase red phosphorus, gas phase white phosphorus and gas phase yellow phosphorus; the thickness of the coated carbon is 2 to 50 nm.

5. A method for synthesizing a black phosphorus carbon negative electrode as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Phosphorus is heated and gasified into gaseous phosphorus, which is catalyzed by a catalyst to generate gaseous black phosphorus, and the gaseous black phosphorus is deposited in porous carbon to obtain black phosphorus porous carbon, which reacts with a reaction gas containing carbon and hydrogen gas to obtain a black phosphorus carbon negative electrode.

6. The synthesis method according to claim 5, characterized in that The temperature of phosphorus heating and gasification is 400℃~1000℃, the temperature of the catalyst is 400℃~600℃, the temperature of the porous carbon is 400℃~600℃, the temperature of the black phosphorus porous carbon reacting with the reaction gas is 400℃~800℃, and the temperature of phosphorus heating and gasification is greater than the temperature of the catalyst and the temperature of the porous carbon.

7. The synthesis method according to claim 5, characterized in that The catalyst comprises an active substance and a carrier, wherein the constituent elements of the active substance comprise tin, phosphorus and iodine, and the carrier is a honeycomb ceramic or carbon material, wherein the carbon material comprises porous carbon, graphite, soft carbon or hard carbon.

8. The synthesis method according to claim 5, characterized in that The hydrocarbon gas includes at least one of acetylene, ethylene, methane and propylene, the reaction gas also includes an inert gas, the inert gas includes at least one of nitrogen and argon, and the volume ratio of the reaction gas to the inert gas is 1:(1-10).

9. A synthesis device for synthesizing the black phosphorus carbon negative electrode as claimed in any one of claims 1 to 4, characterized in that: The invention comprises a black phosphorus-carbon composite device and a coated carbon synthesis device. The black phosphorus-carbon composite device is provided with an independently temperature-controlled phosphorus chamber, a catalyst chamber and a porous carbon chamber in sequence according to the gas flow direction. Sealed valves are provided between the phosphorus chamber and the catalyst chamber, and between the catalyst chamber and the porous carbon chamber. The coated carbon synthesis device comprises one of a fluidized bed device, a rotary kiln device and a tubular furnace device.

10. A battery, characterized in that: It comprises the black phosphorus carbon negative electrode as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Black phosphorus-carbon composite material as well as preparation method and application thereof

    CN116573621A

  • Phosphorus-carbon composite negative electrode material and preparation method and application thereof

    CN117673304A

Cited By

  • Phosphorus-based alloy composite negative electrode material and application thereof in all-solid-state secondary battery

    CN121331805A